Answer:
![\frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
Step-by-step explanation:
Since
have the same denominators, we add them first. We then add
to the result.
Answer:
3x-1
Step-by-step explanation:
6 +(-x) +2x + (-7) + 2x=
6-x +2x -7 + 2x =
6-7+ 2x+2x-x=
-1 + 3x=
3x-1
-3(y+2)^2-5+6y
-3(y^2+4y+4)-5+6y
-3y^2-12y-12-5+6y
-3y^2-6y-17
Answer:
<h2>GCF(10, 45) = 5</h2>
Step-by-step explanation:
![10=2\cdot\boxed{5}\\\\45=3\cdot3\cdot\boxed{5}\\\\GCF(10,\ 45)=\boxed{5}](https://tex.z-dn.net/?f=10%3D2%5Ccdot%5Cboxed%7B5%7D%5C%5C%5C%5C45%3D3%5Ccdot3%5Ccdot%5Cboxed%7B5%7D%5C%5C%5C%5CGCF%2810%2C%5C%2045%29%3D%5Cboxed%7B5%7D)
Answer:
angleB = 41.4°
Step-by-step explanation:
✨ Trigonometry✨
cos theta = adj / hyp
theta = inverse-cos adj / hyp
theta = inverse-cos 12 / 16
theta = inverse-cos .75
theta = 41.4°
*theta is the 0 with a line through it